EIA- A Teacher Education Project in Bangladesh: An Analysis from Diversified Perspectives - Abdul Karim, Abdul Karim; Mohamed, Abdul Rashid; Rahman, Mohammad Mosiur (Eskişehir Osmangazi University, 2017)
English in Action (EIA) is an ongoing teacher education project which places mobile technology at the centre of its action. Most of the studies carried out focused on the changes EIA brought in teachers’ classroom actions. Along with this, they also explored the classroom to observe whether the input given during training program is implemented in real life. No study has been conducted that compares and contrasts the components of mobile learning in general and the components EIA is using. This study, particularly, drew a comparative analysis between the mobile learning and EIA initiated mobile learning to reveal the extent it matched or mismatched to the components of mobile learning. It also scrutinized teachers’ behavior in the classroom after participating in EIA. It also penetrated to find the contents to be reviewed. Qualitative method was used to conduct this study. The result revealed that the components of EIA match to the mobile learning ones to the extent that EIA entails those suiting the context. Few elements were seemed absent as they are less suitable in such context. Besides, teachers were found bringing changes in their classrooms. The introduction of action research and reflective teaching were suggested to add to EIA’s program.